Benthic distribution in small tropical lakes: the presence of macrophytes matters - Shimabukuro, Erika Mayumi; Henry, Raoul [UNESP] (Int Soc Tropical Ecology, 2018)
The objective of this study was to compare the structure of macroinvertebrate communities in two lakes, one with and another without macrophytes (M+ and M-, respectively). Due to the high concentration of macrophytes into the eastern portion of the M+, we expected: (i) spatial heterogeneity of environmental variables and spatial variation of benthic composition in this lake, comparing to M-, and (ii) higher richness into the macrophytal portion (eastern portion of M+), comparing to the free macrophyte portion (western portion of M+), and also a higher richness in M+ in relation to the M-. The study was conducted in two lakes marginal to a river in Southeastern Brazil. Sampling was performed in two periods in ten sites within each lake. Three replicate samples of sediment were collected with a Van Veen grab in each site and period. Abiotic variables of water and sediment were measured at each sampling site. Macrophytes clearly determined two compartments in M+. The taxa richness was higher in the eastern portion of the M+, where the macrophytes where concentrated, and even the western portion of M+ presented higher richness than M-. Chironomus paragigas Reiss 1974 (Chironomidae) predominated in M-, a homogeneous environment. In contrast, several other taxa, such as Cryptochironomus, Cladopelma, Asheum, Dicrotendipes, Procladius occurred exclusively in the lake with macrophytes, a fragmented and heterogeneous environment. Therefore, in this study macrophytes presence induced spatial heterogeneity, reflecting in benthic macroinvertebrates' richness and distribution.
Keywords: Aquatic plants; chironomidae; diversity; macroinvertebrates; organic matter; pond; spatial variation